THERMODYNAMIC ANALYSIS OF WHEAT GLUTEN ON THE BASIS OF ITS HYGROSCOPIC PROPERTIES - E. V. Fomenko; A. H. Ugmanov; O. A. Aleksanyan; T. S. Nguyen (Современная наука и инновации)
For wet thermolabile materials, which include wheat gluten, the static balance between the product and the environment, occurs under the condition that the state of the "wet body - gas" does not change over time under the influence of various internal factors. At this equilibrium, the amount of moisture in the hygroscopic product depends on its type, type and energy of moisture contained in it, and a number of parameters, in particular, the temperature and partial pressure of water vapor over the surface of the product and is important in the study of the hygroscopicity of raw materials.